PERAN KULIAH KERJA MANDIRI MAHASISWA DALAM PEMBERDAYAAN MASYARAKAT DESA POPAYA, KECAMATAN DENGILO, KABUPATEN POHUWATO - Nuzmerini Rauf; Tri Setiawati Maulana; Sarajudin J Ibrahim; Fatma Abdullah; Selawati Yahya; Nuralya I Tialo; Maryam Mailantang; Delvi Lihawa (Journal of Hulonthalo Service Society (JHSS), 2025)
The Independent Community Service Program (Kuliah Kerja Mandiri/KKM) is a form of community engagement carried out by university students as part of the implementation of the Tri Dharma of Higher Education. This program aims to develop students’ competencies while empowering local communities through the direct application of knowledge, skills, and attitudes. This article describes the implementation, methods, and outcomes of the Independent Community Service Program conducted by students of Universitas Bina Mandiri Gorontalo in 2025 at Popaya Village, Dengilo District, Pohuwato Regency. The methods applied in this program included field observation, interviews with village officials and community members, and active student participation in various community-based activities. Based on the village situation analysis, several programs were implemented, including the installation of road direction signs, the creation of waste education boards, integrated health service activities (posyandu), free malaria screenings, environmental clean-up activities, and mini soccer activities in collaboration with local youth organizations. The results indicate that the implementation of the KKM program had a positive impact on increasing community awareness of environmental cleanliness, public health, and social cohesion. Community participation in health services and collective activities increased, and effective collaboration was established among students, village authorities, health workers, and community members. In addition, the program provided meaningful experiential learning opportunities for students to apply academic knowledge and develop social responsibility. Despite challenges such as limited funding, facilities, and weather conditions, all programs were successfully implemented through strong coordination and community support.